IT GOVERNANCE AND THE USE OF AI IN THE FINANCIAL SECTOR: PERSPECTIVES AND CHALLENGES: perspectivas e desafios - Braga, Bruno; Gibertoni, Daniela (Revista Interface Tecnológica, 2025)
It is well known that Artificial Intelligence (AI) has quickly entered all spheres of society, and this tool has been widely used in all sectors to develop faster and, why not, more efficient work. Within the financial market, the use of AI has played important roles, such as predicting market trends, detecting fraud, automating tasks, and even impacting the power of investments. In Information Technology Governance (ITG), the use of AI has been a transformative tool, as it allows for faster, more efficient, and proactive responses to the sector’s demands. This technological advance has also shown its importance in preventing and responding to failures, correcting problems, and increasing efficiency. Given this scenario, the objective of this study is to highlight how the use of AI within the financial sector can bring optimization and efficiency to business, which is extremely relevant, since this area demands the use of extensive technology, which works with real-time access, with large volumes of confidential data and thus needs to be fast, accurate, and secure. The methodology used in this study was a Literature Review, where articles and websites that objectively address the topic of this study were consulted. The results found indicate that the use of AI in all sectors, specifically the financial sector, has great advantages, but that the challenges of using this technology, as well as its disadvantages, must also be considered, given that the financial 2 sector is extremely important, especially because it is, in a way, related to the development of the country’s economy.